Effects of Fluorinated Diluents in Localized High‐Concentration Electrolytes for Lithium–Oxygen Batteries. (25th June 2020) - Kwak, Won‐Jin; Lim, Hyung‐Seok; Gao, Peiyuan; Feng, Ruozhu; Chae, Sujong; Zhong, Lirong; Read, Jeffrey; Engelhard, Mark H.; Xu, Wu; Zhang, Ji‐Guang
Abstract: A stable electrolyte is critical for practical application of lithium–oxygen batteries (LOBs). Although the ionic conductivity and electrochemical stability of the electrolytes have been extensively investigated before, their oxygen solubility, viscosity, volatility, and the stability against singlet oxygen ( 1 O2 ) still need to be comprehensively investigated to provide a full picture of the electrolytes, especially for an open system such as LOBs. Herein, a systematic investigation is reported on the localized high‐concentration electrolytes (LHCEs) using different fluorinated diluents in comparison with those of conventional electrolytes. The physical properties and activation energies for reactions with singlet oxygen ( 1 O2 ) of these electrolytes are calculated by density functional theory. The electrochemical performances of LOBs using these electrolytes are compared. This study reveals that the correlation between the stability of the electrolytes and their physical and electrochemical properties depends strongly on the diluents in LHCEs. Therefore, it shines light on the rational design of new electrolytes for LOBs. Abstract : To find promising electrolytes for more reliable performance of lithium–oxygen batteries (LOBs), various physical and electrochemical properties must be considered, which are discussed through comprehensive and comparative studies of localized high‐concentration electrolytes (LHCEs) using different diluents. An LHCE, which is stable with a lithium metal anode and singlet oxygen, is developed to achieve the long cycle life of LOBs.